Trans bodies, trans selves : a resource by and for transgender communities - Erickson-Schroth, Laura (Oxford University Press, 2022)
"What does it mean to be trans? A common understanding of transgender, or trans for short, is that a person's gender differs from the sex they were assigned at birth. However, many see the idea of being trans as more complicated -- as an active process of challenging the formal structures that govern how gender is defined. For different people, and in different times, places, and contexts, gender itself can be a broad entity or a very narrow one, and in various ways, understandings of "trans" can seem too expansive or too restrictive"--